The contribution of Zn(II) and phosphate anions to the inhibition of organic coating cathodic disbondment on galvanised steel by zinc phosphate pigment. (15th April 2022) - Griffiths, C.M.; Wint, N.; Williams, G.; McMurray, H.N.
Abstract: In-situ scanning Kelvin probe (SKP) measurements are used to investigate the relative contributions of in-coating zinc (II) cations and phosphate anions to the inhibition of corrosion-driven cathodic disbondment by zinc phosphate (ZnPhos) pigments. Using hot-dip galvanized steel (HDG) substrates, delamination rates of model polyvinylbutyral (PVB) coatings comprising different pigment volume fractions (ϕ) of phosphate-loaded hydrotalcite and Zn(II)-exchanged bentonite are compared with those established in the presence of ZnPhos. The most powerful inhibitory effect is obtained using in-coating Zn 2+, while ZnPhos pigments inhibit cathodic disbondment rather weakly and as such the principal function of phosphate is to control Zn 2+ solubility. Highlights: Inhibition of cathodic disbondment by Zinc phosphate investigated on PVB coated HDG. Comparison of efficiency with separate PO 4 3 − and Zn 2+ ion-exchange pigments. Powerful influence of in-coating Zn 2+, but PO 4 3 − far less effective. Principal function of PO 4 3 − in zinc phosphate is to control Zn 2+ solubility.